EFFECT OF DIFFERENT PACKAGING METHODS ON CONSUMERS EATING QUALITY OF BEEF - Ahmedin ABDUREHMAN MUSA (Stefan cel Mare University of Suceava, 2019)
Protecting meat and meat products during the distribution process, including storage and transport, from contamination by dirt, bacteria, moulds, yeasts, parasites, toxins and weight loss are very prominent. The aim of this review was to summarize the effect of packaging on consumers eating quality of beef. If meat is packaged in different packaging methods there may be a change in some beef quality parameters. Three types of packagesl are in general used today i.e. vacuum, atmospheric and active one. If meat is packaged in modified atmosphere with high oxygen content the colour stability of beef increases, but other quality parameters are negatively affected. Vacuum packaging has considerable advantage on all meat eating quality except of colour and purge problem. It has been observed that active packaging systems maintain as well as extend meat eating quality and shelf-life beef.